INVAGINATED SKIN RELEASE OF DOCKING SITE UNDER WALANT; OBSTACLES DURING COVID-19 PANDEMIC - MHM, Hafiz; AR, Zamri; O, Saifudin; B, Norhaslinda; AR, Ahmad (International Journal of Allied Health Sciences, 2021)
Soft-tissue invagination or soft tissue incarceration is a common complication during the late stage of bone transport. We report a case of soft tissue release under wide-awake local anesthesia no tourniquet (WALANT) where operating theater slot is limited in the era of Covid-19 pandemic. A 31-year-old man involved with an accident which resulted in open fracture of right tibia Grade IIIa with 9cm bone loss. Ilizarov external fixator and cortectomy for bone transport was performed to address bone and soft tissues defect. During the bone transport process, noted the transport segment was halted by a soft tissue invagination at distal third of the right leg. Patient underwent soft tissue release under WALANT amidst the pandemic using combination of 1% lidocaine, 1:100,000 epinephrine, and 10:1 8.4% sodium bicarbonate. The solution was infiltrated through field block at area of interest to a maximum safe dose of 40ml dilution. Either an H shape “French Door” release or square excision of skin tissue was performed. No further revision of docking site was performed until union and implant removal. Soft tissue release for skin invagination over the docking site is an effective way to eliminate soft tissue block in bone transport. Conventionally, is done under regional or general anesthesia. We attempted this procedure under WALANT which was previously done for hand and wrist surgeries to address the operating time issue during this pandemic. In conclusion, WALANT is a viable option for skin release and bone resurfacing as it achieved both adequate surgical release as well as patient tolerance with additional advantage of reducing hospital stay.